The Effects of Novel Ingestion of Sodium Bicarbonate on Repeated Sprint Ability. Issue 2 (February 2016) - Miller, Peter; Robinson, Amy L.; Sparks, S. Andy; Bridge, Craig A.; Bentley, David J.; McNaughton, Lars R.
Abstract : Abstract: Miller, P, Robinson, AL, Sparks, SA, Bridge, CA, Bentley, DJ, and McNaughton, LR. The effects of novel ingestion of sodium bicarbonate on repeated sprint ability. J Strength Cond Res 30(2): 561–568, 2016—This work examined the influence of an acute dose of sodium bicarbonate (NaHCO3 ) on buffering capacity and performance during a repeated sprint ability (RSA) protocol. Eleven (mean ± SD : age 24.6 ± 6.1 years; mass 74.9 ± 5.7 kg; height 177.2 ± 6.7 cm) participated in the study, undertaking 4 test sessions. On the first visit to the laboratory, each participant ingested 300 mg·kg −1 of NaHCO3 (in 450 ml of flavored water) and blood samples were obtained at regular intervals to determine the individual times peak pH and HCO3 − . In subsequent visits, participants ingested 300 mg·kg −1 of NaHCO3, 270 mg·kg −1 body mass (BM) of NaCI, or no drink followed by a RSA cycling protocol (10 × 6 seconds sprints with 60 seconds recovery), which commenced at each individuals predetermined ingestion peak pH response time. Blood samples were obtained before exercise and after the first, fifth, and 10th sprint to determine the blood pH, HCO3 −, and lactate (La − ) responses. Total work completed during the repeated sprint protocol was higher ( p ⩽ 0.05) in the NaHCO3 condition (69.8 ± 11.7 kJ) compared with both the control (59.6 ± 12.2 kJ) and placebo (63.0 ± 8.3 kJ) conditions. Peak power output was similar ( p > 0.05) between the 3 conditions. Relative to the control and placebo conditions, NaHCO3 ingestion induced higher ( p ⩽ 0.05) blood pH and HCO3 − concentrations before exercise and during the bouts, and higher lactate concentrations ( p ⩽ 0.05) after the final sprint. Results suggest that NaHCO3 − improves the total amount of work completed during RSA through enhanced buffering capacity.